Tropical teleconnections through the Amundsen Sea Low impact Antarctic toothfish recruitment within the Ross Gyre - Erik Behrens; Arnaud Grüss; Matt Pinkerton; Steve Parker; Graham Rickard; Craig Stevens (Scientific Reports)
Abstract Antarctic toothfish (Dissostichus mawsoni) in the Ross Sea region are believed to spawn predominantly in the northern parts of the Ross Gyre during the austral winter with fluctuations in their recruitment observed. This Lagrangian modelling study attempts to explain these fluctuations and shows how sea-ice drift impacts the buoyant eggs and the overall recruitment of juveniles reaching the Amundsen shelf break. Interannual variations in the Amundsen Sea Low, linked to tropical sea surface temperatures, cause modulations in the sea-ice drift and subsequent recruitment. When the Amundsen Sea Low is weaker, consistent with El Niño conditions, the northward sea-ice drift reduces, and more eggs remain within the Ross Gyre leading to a larger recruitment success. Conversely, recruitment success reduces during La Niña conditions. The sea-ice drift may explain about 80% of the interannual Antarctic toothfish recruitment variability over the period 1975–2016 and is of particular importance during the first year after spawning. These results enable future interannual changes in Antarctic toothfish recruitment success based on remote observations to be anticipated. Our findings suggest that ongoing climate change strengthening of the Amundsen Sea Low, will likely contribute to a long-term toothfish recruitment decline in the Ross Gyre region.